Возвращение классов? Перспективы классового анализа постсоветской реальности - Куценко, О. (Социология: теория, методы, маркетинг, 2001)
The author considers the gnosiological perspectives of class concept for study of post-Soviet transformation, and supports the conclusion about the essential role of classes in the High Modernity era. The Marxist and Weberian sociological heritage is considered as a background of class analysis and revised on the mutual complementary principles. Such revise lies in the structural-agency framework, which is realized although differently both by A.Giddens and P.Bourdieu in the contemporary sociology. Such a class concept reflects a social power (capacity) of the big social formations which have unequal locations into the main social resources that determine their life chances, social dispositions and practice, social claims and capacity of the common (cooperative) actions. The macro structural class divisions concretize in those social resources and life chances which flux from the individual civic, market and work situation. The diathropical and emergency nature of class is increased under the period of quick social change. There are numerous class positions forming in contemporary Ukrainian social space which accumulate social power (capacity) and can dichotomize the post-Soviet society.